Germination and breaking seed dormancy of Alpinia malaccensis - REZA RAMDAN RIVAI; FITRI FATMA WARDANI; MICHA GRACANNA DEVI (Nusantara Bioscience, 2015)
Abstract. Rivai RR, Wardani FF, Devi MG. 2015. Germination and breaking seed dormancy of Alpinia malaccensis. Nusantara Bioscience 7: 67-72. Alpinia malaccensis belongs to the ginger family, Zingiberaceae, and is generally propagated by vegetative organs. Seed propagation is needed in order to improve the quality of plants through crossbreeding. The hard testa and small endosperm are the main problems in seed germination. The objectives of this research were to determine the best media for germination and method for breaking seed dormancy of A. malaccensis. The research was conducted at the Seed Conservation Laboratory, Center for Plant Conservation Bogor Botanic Gardens. A Completely Randomized Design with three replications was used, and the two treatment factors were different germination media and the methods of breaking seed dormancy. Results showed that cocopeat was the best media for increasing A. malaccensis germination rate one month after planting, whereas the method of wounding the testa or soaking the seed in water with a temperature of 75 oC for 5 minutes showed the highest rate of A. malaccensis germination after three months of planting.